Safety of new indigenous human Rabies Monoclonal Antibody (RMAb) for Post Exposure Prophylaxis - Shivalingaiah, Anwith Huluvadi; Shankaraiah, Ravish Haradanhalli; Hanumanthaiah, Ashwath Narayana Doddabele (Indian Journal of Community Health, 2018)
Background: WHO recommended development of Rabies Monoclonal Antibodies (RMAb) to overcome the problems associated with rabies immunoglobulin for post exposure prophylaxis against rabies in all category III exposures. A new indigenous RMAb has been manufactured and marketed in India. The present study was conducted to monitor the post marketing clinical use of RMAb for post exposure prophylaxis. Aims & Objectives: To assess the safety of human rabies monoclonal antibodies for post exposure prophylaxis. Material & Methods: A comparative study between the new RMAb and the previously established rabies immunoglobulins was conducted at anti-rabies clinic in a Medical college Hospital, Bangalore from January to June, 2018. All the animal bite victims with category III exposure were included in the study. The details regarding their socio demographic profile, characteristics of exposure, post exposure prophylaxis provided and any adverse drug reactions following administration of RMAb were recorded. Results: The study included 397 subjects with category III exposure; 142 in RMAb group, 243 in equine rabies immunoglobulin group & 12 in human rabies immunoglobulin group. Majority of the study subjects were males & aged between 1 – 85 years. All the subjects were provided post exposure prophylaxis as recommended by WHO. There were no immediate adverse drug reactions; however, 8% of the subjects had delayed ADRs such as pain at the site of infiltration (4.2%), swelling (2.1%) and wound infection (0.7%); which resolved without any complications. Conclusion: The new indigenous human RMAb is safe for post exposure prophylaxis against rabies.